The Effectiveness of Herringbone Strategy to Increase Student’s Reading Comprehension of Descriptive Texts at Seventh Grade Students of SMAN 4 Bangkalan - Moh. Arief Wahyudi (SELL Journal : Scope of English Language Teaching, Linguistics, and Literature, 2018)
Reading is one of the skills taught in school or university. Because reading, students will get some information; enrich the knowledge so that it can develop their idea. The aspect of comprehending texts, students do not only understand the meaning, vocabulary and grammar but also shall be more than. The researchers held the previous of observations at Seventh Grades of SMAN 4 Bangkalan. They have had problems to comprehend a text in getting information, content of the text and develop ideas. Because they do not comprehend the meaning of every word in English sentence so they feel boring. The Herringbone strategy is a solution because it is a step in making a designed the drafted of wreath frame to help classify information from text. This strategy can be applied a descriptive text. Whatever using the Herringbone strategy can be effectively to improve on the reading comprehension in descriptive texts. The used method is the quantitative, the test instrument by using Quasi at pre-and post- test and the total number of the population of 80 students in two classes, the samples taken of 40 students because it is a homogenous class. The treatment was done twice times. After the post-test is carried out on the experimental class then retrieved the value of the average (Mean) = 26.77; Median = 26; Mode = 25; and Standard Deviation = 1.746. Based on the calculation value obtained results of 0.5 are included in adequate medium, then it can be inferred that the technique is effective in comprehending Herringbone strategy in descriptive texts. So Ha had stated that the using Herringbone strategy in comprehending a text was effective than without the using of the Herringbone strategy was rejected in Ho.